Migrant Dwelling in Greater Santiago: Housing, Networks and Overcrowding [Habitar Migrante en el Gran Santiago: Vivienda, Redes y Hacinamiento] - Margarit-Segura, D (Universidad de Chile, Instituto de la Vivienda, 2022)
One of the distinctive aspects of the migrants’ settlement in the destination territories is their concentration in metropolitan areas and, within them, in certain territorial areas. The article proposes problematizing migrant living through the dimensions of housing, home, and location of migrants residing in Greater Santiago, which allows us to understand the ongoing migratory phenomenon by identifying, through the overcrowding variable, the intangible social resources associated with social, cultural, and economic capitals that circulate in family and non-family networks. The methodological strategy is quantitative in nature, it uses statistical sources from the 2017 Census and the results of the Migrant Voices (VM) survey, carried out by the Jesuit Migrant Service (2019). The main results are aimed at understanding that migrant dwelling associated with overcrowding, despite presenting elements of precariousness and social vulnerability, could also expose family strategies of mutual support and care among the migrant population in the receiving societies. © 2022, Universidad de Chile, Instituto de la Vivienda. All rights reserved.